2020
DOI: 10.1002/app.49171
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and dimensional performance of poly(lactic acid) 3D‐printed parts using thin plate spline interpolation

Abstract: In additive manufacturing, determining the correct deposition parameters is very important as this can affect the final properties of printed parts. Since there is no agreement on the optimal level of the different printing parameters in reported results, this work evaluated the influences of layer thickness (LT), deposition speed (DS) and printing direction (PD) on tensile properties and dimensional accuracy of poly(lactic acid) 3D parts evaluating the possibility of using thin plate spline interpolation meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…(2) The adjacent deposited filaments cause the air gap between interlayers. (3) The thermal history of materials affects the interfacial bonding of products 36 . Optimal 3D printing parameters can make the molecular chains between adjacent layers entanglement stronger, reducing the porosity and improving the mechanical properties of 3D printing products.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The adjacent deposited filaments cause the air gap between interlayers. (3) The thermal history of materials affects the interfacial bonding of products 36 . Optimal 3D printing parameters can make the molecular chains between adjacent layers entanglement stronger, reducing the porosity and improving the mechanical properties of 3D printing products.…”
Section: Resultsmentioning
confidence: 99%
“…Polynomial fit p55, Equation ( 4), was applied simultaneously to the experimental and the interpolated data to obtain a 3D surface that correlates MV, composition, and time, Equation (3). [10], [11] (4)…”
Section: Tpsim and Polynomial Fitting -Fluid Incorporation Studymentioning
confidence: 99%
“…[8], [9] This method was used to calculate and estimate the torque values through rheometric tests and to evaluate the effect of parameters layer thickness, [10] deposition speed and printing direction on tensile properties and dimensional accuracy of PLA 3D printed parts. [11] The aim of this work was studied the mass variation (MV) of chitosan/ PAA in Dersani® oil and physiological saline solution using the TPSIM was used to evaluate the effect of time and composition in the fluid absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Neither in terms of the variation trend could there be found agreement in the previous research analyzed. In this regard, whilst most of the researchers found that the UTS of the parts manufactured by FFF is increasing with the decrease in the layer height [ 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], others concluded the opposite [ 14 , 35 , 36 ] or defined optimal values of this variable, situated inside a variation interval that was set for the optimization of the selected printing parameters [ 37 , 38 , 39 , 40 , 41 ]. These different or even controversial opinions could be explained by the fact that the chosen combinations of process parameters determined completely different thermal printing conditions as well as the distinct values adopted for the layer thickness, situated within a wide range (0.06 mm–0.6 mm) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%